Legal Protection For Personal Data In The World Of Work In The Era Of Digitalization Of Technology And Information - Ambar Rani Priyanjani; Farah Fadillah; Alfazrryan Ghalib; Endang Sutrisno; Deni Yusup Permana (Al-Makki Publisher, 2024)
Legal certainty is one of the objectives of law according to Gustav Radburch, with the development of the times, and the rise of digitalization, it is necessary to have a legal umbrella as a form of preventive effort so that there are no legal problems such as misuse of personal data in the labor scope. This legal research method uses normative juridical legal methods using qualitative data based on consideration of the purpose of this research itself to determine the importance of legal certainty and protection of personal data in the context of labor in the era of technology, and information that has developed rapidly. The clarity of legal norms guides community behavior, including the protection of personal data. The impact of technological advances is especially evident in changes in community behavior and information seeking through the internet. This change creates new challenges, especially related to the misuse of personal data in the world of work. Legal protection for personal data in the world of work in the era of digitalization of technology and information is very important. It has positive implications for companies, employees, and society as a whole. By implementing good personal data protection, all parties can benefit from the opportunities offered by digital technology while maintaining the privacy and security of personal data.